Propolis nanoemulsion extract from celebes stingless bee (Tetragonula biroi) phytochemistry and antibacterial analysis to periodontopathogen bacteria - Nadya Rafika Amalia; Theresia Indah Budhy; Rini Devijanti Ridwan; Devi Rianti; Taufan Bramantoro; Muhammad Luthfi; Nastiti Faradilla Ramadhani; Adya Pramusita; Nurul Aisyah Rizki Putranti; Albertus Putera Nugraha; Putri Cahaya Situmorang; Khairul Anuar Shariff; et al. (Journal of Oral Biology and Craniofacial Research)
Background: Propolis from Sulawesi's stingless bees (Tetragonula biroi) contains antioxidants, more flavonoids than propolis from Apis bees, and the antibacterial ability. Objective: to examine the antibacterial properties of Propolis Nanoemulsion Extract (PNE), which is extracted from the Celebes Stingless Bee (T. biroi), in relation to the periodontopathogen bacteria such as Fusobacterium nucleatum (Fn), Porphyromonas gingivalis (Pg), Aggregatibacter actinomycetemcomitans (Aa), and Provotella intermedia (Pi). This investigation also examines PNE's phytochemistry, particle size analysis (PSA), and zeta potential. Methods: The maceration process with 96 % ethanol was used to create PNE from Celebes stingless bee (T. biroi), which was then subjected to zeta potential measurement and PSA. Phytochemical analysis was used to identify phytochemical constituents in the PNE (T. biroi). Diffusion zone, minimum bactericidal concentration (MBC), and minimum inhibitory concentration (MIC) were used to assess antibacterial efficacy against Aa, Pg, Pi, and Fn. Furthermore, the statistical analysis was used to extract the data. Results: Phenols, alkaloids, and flavonoids were identified; however, triterpenoids and saponins were not. Between 151.28 and 182.2 diameter nanometers (d.nm) was the range of the PNE's diameter. At 1.56 % propolis (T. biroi) concentration, the MIC, MBC, and diffusion zone analysis performed better than at 0.76 %, with a significant difference (p:0.01; p < 0.05) to Aa, Pg, Pi, and Fn. Conclusions: The highest antibacterial activity against Aa, Pg, Pi, and Fn as periodontopathogen bacteria is demonstrated by alkaloids, flavonoids, and phenols in PNE from Celebes (T. biroi) at a concentration of 1.56 %.